Blended Learning Strategies: Integrating E-Learning to Improve Teaching and Learning Outcomes - Nadya Berkian; Abd. Rajab (Mauve Journal De Leardu, 2025)
This study examines the integration of blended learning strategies as a means to improve teaching and learning outcomes in higher education. Drawing on a case study approach, data were collected through interviews with lecturers and students, classroom observations, and document analysis to explore experiences, benefits, and challenges of combining e-learning with face-to-face instruction. The findings reveal that blended learning enhances flexibility, promotes learner autonomy, and enables more interactive classroom engagement, allowing students to access materials at their own pace and fostering greater inclusivity in participation. However, the study also identifies significant challenges, including the additional workload for instructors in preparing digital content and inequities faced by students with limited internet access, which highlight that blended learning is not merely a technological innovation but a systemic transformation. The discussion emphasizes the importance of aligning blended learning with institutional readiness, pedagogical innovation, and infrastructural investment. Overall, the study concludes that blended learning holds transformative potential for higher education when supported by effective instructional design, faculty development, and equitable access to digital resources.